2017
DOI: 10.1161/circresaha.116.309006
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-Linked Pathophysiological Alterations in the Gut

Abstract: Rationale Sympathetic nervous system control of inflammation plays a central role in hypertension. The gut receives significant sympathetic innervation, is densely populated with a diverse microbial ecosystem, and contains immune cells that greatly impact overall inflammatory homeostasis. Despite this uniqueness, little is known about the involvement of the gut in hypertension. Objective Test the hypothesis that increased sympathetic drive to the gut is associated with increased gut wall permeability, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
465
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(500 citation statements)
references
References 55 publications
24
465
3
8
Order By: Relevance
“…Changes in microbiota have been associated with alterations in gut pathology in animal models of HTN [12]. However, little is known about gut microbiota and its relationship with gut barrier function in patients with HBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in microbiota have been associated with alterations in gut pathology in animal models of HTN [12]. However, little is known about gut microbiota and its relationship with gut barrier function in patients with HBP.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate a strong correlation of SBP with gut bacteria and barrier dysfunction, which may provide important clues to the role of microbiome in HTN. We have previously shown that increased gut sympathetic nerve activity and reduced gut tight junction proteins precede development of HTN in spontaneously hypertensive rats [12]. Together, it is tempting to speculate that prohypertensive signals (diet, salt, environment, toxins etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With aging of the intestinal epithelium, ischemic changes, low-grade inflammation and the increased use of nonsteroidal anti-inflammatory drugs hamper the normal function and regenerative capacity of the epithelial barrier which can lead to a mucosal injury [26] [42]. In addition, hypertension has been proposed to induce a low-grade inflammation in the gut epithelium [43]. We hypothesized that inflammatory changes could be balanced with increased corticosterone production, but no correlation was found between these two variables.…”
Section: Discussionmentioning
confidence: 99%
“…Gut receives significant sympathetic innervation. Monica M et al [32] demonstrated that in hypertension, the gut changed pathologically and associated with alterations in microbial communities. The dysfunction of sympathetic-gut communication is associated with gut pathology, dysbiosis and inflammation, last but not least, relevant to hypertension.…”
Section: Animal Modelmentioning
confidence: 99%